KONSTRUKSI SOSIAL UANG PANAI PADA PERKAWINAN SUKU BUGIS DI KOTA DENPASAR - Amiruddin Jalil, Andi Ahmad; Zuryani, Nazrina; Krisna Aditya, I.G.N Agung (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 1 No 01 (2021): JISSOROT, 2021)
The Bugis ethnic community has traditions and customs that are maintained whenabroad in Denpasar City, for example thetradition traveling panai money in the process of carrying out marriages. This study aims to explain how the stages of determining panai money and how the social construction of panai money in Bugis marriages in Denpasar City. Thetradition is panai money still carried out and maintained in the process of carrying out marriages as an ancestral heritage inherent in the Bugis community in Denpasar City and implies the seriousness and ability of the man to give respect or appreciation, prosperity and welfare for the woman he wants to marry as well as maturity. the men to be able to enter the level of marriage must be prepared with various problems that will be faced later in marriage so that the meaning of panai money is still being constructed to the next generation.   Keywords: Panai money , social construction, marriage, Bugis people